Cartilage tissue engineering with controllable shape using a poly(lactic-co-glycolic acid)/collagen hybrid scaffold. (May 2013) - Dai, Wenda; Yao, Zhenjun; Dong, Jian; Kawazoe, Naoki; Zhang, Chi; Chen, Guoping
It is of critical importance to prepare three-dimensional biodegradable porous scaffolds for cartilage tissue engineering. We developed a poly(lactic- co -glycolic acid)/collagen hybrid scaffold, which combined the advantages of natural type I collagen and synthetic polymer polylactin 910 knitted mesh (90:10 copolymer of glycolic acid and lactic acid), and a method using this poly(lactic- co -glycolic acid)/collagen scaffold to regenerate cartilage with controllable shape. The mechanically strong poly(lactic- co -glycolic acid) mesh served as a mechanical skeleton supporting the scaffold, and the collagen benefited cell seeding, distribution, and tissue formation. Bovine chondrocytes were cultured in the hybrid scaffold and transplanted into the subcutaneous sites of nude mice for 4 weeks. All the samples showed spatially uniform cell distribution, natural chondrocyte morphology, and deposition of abundant cartilaginous extracellular matrices such as type II collagen and aggrecan. Production of glycosaminoglycans per DNA reached 74.63% of the natural articular cartilage. The mechanical strength was 62.76% and 71.43% in Young's modulus and stiffness, respectively, compared to the native articular cartilage. All the samples successfully maintained the original shapes. Our method provides a new strategy for regeneration of cartilage tissue with designed shapes.